Green Marketing and Green Brand Image on Users-Attitudes of The Body Shop Indonesia - Ida Lestari; Fitriani, Dinda Rakhma (Publisher Cv. Inara, 2021)
This study aims to determine the effect of Green Marketing and Green Brand Image on users attitudes of The Body Shop Indonesia products empirically, either partially or simultaneously. The population in this study are followers of the Instagram account @thebodyshopindo who have purchased The Body Shop products and used them. This study used a sample of 100 respondents where the questionnaire was distributed using google form through social media Instagram. Sampling using purposive sampling method. The data analysis method used multiple linear regression, with partial and simultaneous hypothesis testing and processed using SPSS version 25 for Windows. The results showed that the two independent variables, namely Green Marketing and Green Brand Image, had a positive and significant effect either partially or simultaneously on the dependent variable of user attitudes. In addition, this study explains that user attitudes are influenced by 68.5% by Green Marketing and Green Brand Image, the remaining 31.5% is influenced by other factors.